The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2147/cia.s66416
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of traditional Thai massage in decreasing spasticity in elderly stroke patients

Abstract: PurposeTo study the efficacy of traditional Thai massage (TTM) versus conventional physical therapy (PT) programs in treating muscle spasticity, functional ability, anxiety, depression, and quality of life (QoL) in Thai stroke patients.MethodsThis randomized controlled trial with a blinded assessor was carried out at the Department of Rehabilitation Medicine, Siriraj Hospital (Bangkok, Thailand). The study included 50 stroke (onset ≥3 months) outpatients experiencing spasticity at the elbow or knee muscles at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The main treatments of stress include psychiatric treatment and pharmacotherapy. Another choice that has been suggested to reduce stress is massage [ 16 , 17 ]. Traditional Thai massage (TTM) is an alternative treatment using the thumbs to apply deep massage, often combined with muscle stretching at the end of the session.…”
Section: Introductionmentioning
confidence: 99%
“…The main treatments of stress include psychiatric treatment and pharmacotherapy. Another choice that has been suggested to reduce stress is massage [ 16 , 17 ]. Traditional Thai massage (TTM) is an alternative treatment using the thumbs to apply deep massage, often combined with muscle stretching at the end of the session.…”
Section: Introductionmentioning
confidence: 99%
“…The PRISMA diagram ( Figure 1 ) summarizes the results of the scientific literature search and 18 randomized controlled trials were included [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. No author responded when contacted for additional information.…”
Section: Resultsmentioning
confidence: 99%
“…14 It has also been found that traditional Thai massage can decrease spasticity, increase functional ability, and improve post-stroke quality of life. 15 …”
Section: The Solutionmentioning
confidence: 99%